Oersted Lecture 2014: Physics education research and teaching modern Modern Physics - Zollman, Dean A. (My University, 2016)
Modern Physics has been used as a label for most of physics that was developed since the discovery of X-rays in 1895. Yet, we are teaching students who would not use the label "modern" for anything that happened before about 1995, when they were born. So, are we and our students in worlds that differ by a century? In addition to content, sometimes our students and we have differing views about methods and styles of teaching. A modern course in any topic of physics should include applications of contemporary research in physics education and the learning sciences as well as research and developments in methods of delivering the content. Thus, when we consider teaching Modern Physics, we are challenged with deciding what the content should be, how to adjust for the ever increasing information on how students learn physics, and the constantly changing tools that are available to us for teaching and learning. When we mix all of these together, we can teach modern Modern Physics or maybe teach Modern Physics modernly. © 2016 American Association of Physics Teachers.
Citation: Zollman, D. (2016). Oersted Lecture 2014: Physics education research and teaching modern Modern Physics. American Journal of Physics, 84(8), 573-580. doi:10.1119/1.4953824